2020
DOI: 10.3390/md18070367
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive GCMS and LC-MS/MS Metabolite Profiling of Chlorella vulgaris

Abstract: The commercial cultivation of microalgae began in the 1960s and Chlorella was one of the first target organisms. The species has long been considered a potential source of renewable energy, an alternative for phytoremediation, and more recently, as a growth and immune stimulant. However, Chlorella vulgaris, which is one of the most studied microalga, has never been comprehensively profiled chemically. In the present study, comprehensive profiling of the Chlorella vulgaris metabolome grown under normal culture … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…This approach offers new ways of exploring the metabolome of biological samples by providing essential analog knowledge among the metabolites identified. Numerous MN applications in microalgae chemistry have been documented in recent years [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach offers new ways of exploring the metabolome of biological samples by providing essential analog knowledge among the metabolites identified. Numerous MN applications in microalgae chemistry have been documented in recent years [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative identification highlights that C. vulgaris species could serve both as a good nutrition source when incorporated into diets, and a potential candidate for biodiesel production, since the amount and ratio of saturated and unsaturated FAs is fundamental to whether microalgae can be used as a biofuel feedstock. Our data are entirely according to the literature [ 36 , 37 , 38 , 39 ]. Furthermore, the qualitative identification confirmed that the use of sulfuric acid was not only adequate for the break of the cell walls but also it was helpful for the complete hydrolysis of all lipids present in the microalgae.…”
Section: Resultsmentioning
confidence: 99%
“…The MS data were firstly converted into the mzXML format using the MSConvert software. The generated spectral information was then uploaded to MZmine-2.5.3-Windows to generate the MS/MS data [ 57 , 58 ].…”
Section: Methodsmentioning
confidence: 99%